DNA methylation of food sensitization in a French-Canadian population - Bénédicte L. Tremblay; Anne-Marie Madore; Catherine Laprise (Clinical Epigenetics)
Abstract Background Food allergy (FA) is a great public health concern with an increased prevalence in the last decades. The underlying development mechanisms of FA and food sensitization (FS), which represents the first stage of development of FA, are influenced by environmental, epigenetic, and genetic factors. DNA methylation is an important epigenetic mediator of gene–environment interactions and key to understanding these mechanisms. Studies have linked whole-genome DNA methylation profile to FA and FS, but they all use methylation arrays. Methylation sequencing captures target regions of methylome with an extensive coverage. Thus, our objective was to identify CpG sites in genome-wide immune regulatory regions associated with FS and test their association with genetic variants using methylation quantitative trait loci (mQTL) analysis in French-Canadian individuals. Results In 114 individuals from the Saguenay–Lac-Saint-Jean asthma family cohort, a total of 10 CpG sites out of 5,233,004 CpG sites were associated with the FS status (P < 1 × 10–8). CpG sites were located in 10 genes (ARRDC1, B9D1, CFL1, CROCC, DHX36, DND1, PMS1, RASSF1, TOP2A, and USP21) all of which were associated with immune response and allergic diseases (allergy, asthma, atopic dermatitis, and allergic rhinitis) in the literature. Almost all individuals with FS clustered based on the methylation levels of these CpG sites which reinforces their importance and relevance to discriminate individuals with and without FS in our cohort. Among the top 10 most significant CpG sites, five were associated with 478 genetic variants in trans-mQTL (FDR < 1 × 10–8). Conclusions To our knowledge, this is a unique association study between FS and DNA methylation using targeted bisulfite sequencing across the genome. This approach provides high-resolution assessment of genome-wide functional methylome that yields valuable understandings to this field of research. The results reveal potential relationships between FS, CpG sites, and genetic variants located in genes involved in allergic diseases. This provides potential insights on the underlying effects of DNA methylation and genetic variants on FS and possibly the pathogenesis of FA. Further epigenome-wide studies on larger samples combined with genome-wide genotyping are needed to validate the results and verify the biological potential of these CpG sites.